PENGARUH INTENSITAS MEMBACA ASMAUL HUSNA TERHADAP KECERDASAN SPIRITUAL DAN KECERDASAN EMOSIONAL SANTRI YAYASAN AT TAQWA METESEH TEMBALANG SEMARANG - Iman Fadhilah; Anas Rohman; Muhammad Burhanuddin (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2022)
Abstract :Asmaul Husna can be interpreted as a good name, the name of Allah is good and the best is 99 contained in the Qur'an, besides that we are commanded by Allah to dhikr and pray by calling Allah's most beautiful names. Because it is characterized as good names so that Asmaul Husna is not only good but also commendable when compared to others. The results showed (1) The intensity of reading Asmaul Husna at the At Taqwa Meteseh Foundation in Tembalang Semarang is in a fairly good category because the intensity of Asmaul Husna affects spiritual intelligence and emotional intelligence by 0,34,6% so that the rest is influenced by other factors. (2) The calculation results obtained rcount of 12.65 and rtable of 3.32 at a significance level of 5% and rtable at a significance level of 5.39. The results of these calculations indicate that there is a significant positive correlation between the variable of reading intensity of Asmaul Husna (X) and the variable of spiritual intelligence (Y1) and the variable of emotional intelligence (Y2) is included in the moderate category. (3) The influence of the intensity of reading Asmaul Husna on the spiritual intelligence and emotional intelligence of the At Taqwa Meteseh Foundation Santri Tembalang Semarang.Keywords: Intensity of Reading Asmaul Husna, Spiritual Intelligence, Emotional Intelligence